From Social Assistance to Control in Urban Margins: Ambivalent Police Practices in Neoliberal Chile [Da Assistência Social Ao Controle Nas Margens Urbanas: Práticas Policiais Ambivalentes No Chile Neoliberal] - Dammert-Guardia, L (Universidade Federal do Rio de Janeiro, 2022)
Crime increase in Latin America has occurred in parallel with a change in police policy in territories. Along with the processes of militarization and police repression, strategies of co-production have been inspired by community policing, but the articulation of both in urban margins has been understudied. Our hypothesis affirms the coexistence and ambivalence of both social assistance and abusive practices against the city s poor. Qualitative methods conducted in Santiago, Chile, show police policy involves both dimensions, which are strongly rooted in identity elements of the military tradition of the region s police forces. © 2022 Universidade Federal do Rio de Janeiro. All rights reserved.